Reforming the Doctrine of God. By F. LeRon Shults - Vogel, Jeff (The journal of theological studies, 2007)
‘The phrase “reforming theology”’, F. LeRon Shults writes in the introduction to Reforming the Doctrine of God, ‘indicates both the dynamic reconstruction of theology and the reformative dynamics of theology’ (p. 4). His interest throughout the book is not merely in the shuffling around of ‘ideas in conceptual space’, but in the liberation of theology from language and concepts that he believes hinder the proclamation of the Gospel in contemporary society., Shults contends that developments in ‘late-modern’ philosophy and biblical studies have contributed to the collapse of certain ideas central to the ‘modern’ doctrine of God, of which he focuses on three: God as immaterial substance, God as single subject, and God as first cause.